Evaluation of medicinal turpentine used for the prevention of bovine babesiosis in southern KwaZulu-Natal and the eastern Free State - Carrington, Christopher Antony Paul (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2011.